2021
DOI: 10.1075/bpa.12.08hop
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and grammatical learning in second language sentence processing

Abstract: With a focus on grammatical processing, the chapter surveys recent studies that investigate how second language (L2) learners learn to predict and whether they use prediction for learning the L2 grammar. This chapter first reviews theoretical approaches to the roles of prediction and prediction error as learning mechanisms in first language (L1) and L2 processing. Drawing on priming, (visual-world) eye-tracking and reading-time data, I then discuss how adult L2 learners may differ from monolingual speakers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 81 publications
5
9
0
Order By: Relevance
“…One possibility is that non-native speakers are limited in their ability to use plausibility information during L2 reanalysis processes (and in L2 structural processing more generally) in cases when they are unable to efficiently execute lower-level language processing, and lexical processing in particular. Such a proposal would be consistent with the lexical bottleneck hypothesis (see, for example, Hopp, 2018), which holds that non-native speakers’ inability to demonstrate native-like structural processing often stems from lexical processing difficulties in the L2. Specifically, this model posits that more effortful lexical processing in the L2 can overload computational capacities, leading to delays or disruptions in L2 structural processing.…”
Section: Discussionsupporting
confidence: 68%
“…One possibility is that non-native speakers are limited in their ability to use plausibility information during L2 reanalysis processes (and in L2 structural processing more generally) in cases when they are unable to efficiently execute lower-level language processing, and lexical processing in particular. Such a proposal would be consistent with the lexical bottleneck hypothesis (see, for example, Hopp, 2018), which holds that non-native speakers’ inability to demonstrate native-like structural processing often stems from lexical processing difficulties in the L2. Specifically, this model posits that more effortful lexical processing in the L2 can overload computational capacities, leading to delays or disruptions in L2 structural processing.…”
Section: Discussionsupporting
confidence: 68%
“…More specifically, these questions were posed to determine whether difficulty in processing Spanish mood (if evident) is caused by generalized difficulty with the syntax and morphosyntax of the form, as proposed by the Shallow Structure Hypothesis (Clahsen & Felser, 2006, or alternatively, such difficulty is an indirect effect of lower level factors that affect the processing of individual lexical items, as proposed by the Lexical Bottleneck Hypothesis (Hopp, 2018). Results that reflect a lack of online sensitivity to mood in all contexts, regardless of verb regularity, would support theoretical claims of difficulty with syntax and morphosyntax (Clahsen & Felser, 2006, whereas a role for verb regularity would support the claim that the primary difficulty arises at the word level (Hopp, 2018). 1 1 It should be noted that the Shallow Structure Hypothesis proposes an increased role for lexical information as a way of compensating for difficulty in the L2 processing syntax and morphosyntax and, on the surface, this claim may sound like it would also be supported by a role for verb regularity in the processing of the subjunctive because word form information is stored in the lexicon.…”
Section: The Spanish Subjunctive In Adult Second Language Acquisitionmentioning
confidence: 99%
“…In a closely related theory, Cunnings (2017) has proposed that the primary limitations lie not in syntax and morphosyntax, but in a greater susceptibility to interference during retrieval from memory, although the empirical predictions of the two theories are often the same. However, the Lexical Bottleneck Hypothesis (Hopp, 2014(Hopp, , 2018 proposes that online effects that appear to indicate an issue with syntax and morphosyntax in sentence processing can in reality be indirect effects of difficulty with lexical access (Hopp, 2017a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers have argued that the strength of prediction is influenced by statistical contingencies between stimuli, and that the parser adapts to the input to maximize the utility of prediction and reduce the costs of potential prediction errors (e.g., Kuperberg & Jaeger, 2016). More recently, studies have shown evidence of adaptation in L2 predictive processing, but also hint at L1/L2 differences in adaptation (e.g., Foltz, 2021aFoltz, , 2021bHopp, 2021). Consequently, the utility of prediction has been discussed as another factor with the potential to explain the inter-and intra-individual variability of prediction (e.g., Grüter & Rohde, 2021;Kaan & Grüter, 2021).…”
Section: L1/l2 Differences In Cue Weightingmentioning
confidence: 99%